Students’ engagement in school and family variables: A literature review - Veiga, Feliciano Henriques (2016)
"Students' engagement in school" is regarded in the literature as a current and valued construct despite the lack of empirical studies on its relationship with specific family variables. The present research aimed to survey studies on the correlation between students' engagement in school and family contexts, specifically in terms of the following variables: perceived parental support, socioeconomic and sociocultural levels, perceived rights, and parental educational styles. In order to describe the state of the art of student's "engagement in school" and "family variables", a narrative review was conducted. The studies reviewed highlight the role of family as a context with significance in student's engagement in school. However, further research is needed to deepen the knowledge of this topic considering potential mediator variables, either personal or school variables. It was also found the need for a psychosocial intervention aimed at providing support for the students coming from adverse family contexts who exhibit low level of engagement associated with poor academic achievement and a higher probability of dropping out.